MANAGING PRIMARY SCHOOL STUDENTS' INTEREST IN TECHNOLOGY DURING CLASSROOM AND EXTRACURRICULAR ACTIVITIES - N. Khushbokova (American Journals, 2023)
This article briefly discusses the pedagogical features of forming the needs of primary school students for technology.
Keywords: innovative technology, natural materials, individual skills, educational tools, technical tools, heuristics, problem situations.